An Analysis of the Grammatical Errors in Narrative Writing Made by Eleventh-grade Students of One Private Islamic Senior High School Palembang, South Sumatera, Indonesia - MURDIYANA MURDIYANA (Faculty of Tarbiyah and Teaching Sciences, Universitas Islam Negeri Raden Fatah Palembang, 2019)
This study was aimed at finding out: (1) the types of grammatical errors in narrative writing made by eleventh-grade students of one private Islamic senior high school Palembang, South Sumatera, Indonesia and (2) the most frequent type of grammatical errors in narrative writing made by eleventh-grade students of private Islamic senior high school Palembang, South Sumatera, Indonesia. This study was a descriptive qualitative research. The data were collected from narrative writing written by the 32 eleventh grade students. In this study, grammatical items analyzed were covering noun, pronoun, verb, conjunction, adjective, adverb and preposition. In analyzing students’ errors, some procedures of error analysis were applied. They were identification, description, and explanation. The frequencies of errors were calculated in percentages. Based on the result of the analysis, there were 621 grammatical errors found in students’ narrative writing. Errors in using verb became the most frequent type of errors with 308 errors (49.59%), followed by errors in pronoun with 136 errors (21.90%), in adjective with 87 errors (14.00%), in preposition with 61 errors (9.82%), in noun with 13 errors (2.09%), in conjunction with 10 errors (1.61%) and the last errors in adverb with 6 errors (0.96%).